A dedicated surveillance network for congenital toxoplasmosis in Greece, 2006-2009: assessment of the results. - Aptouramani, Maria; Theodoridou, Maria; Syrogiannopoulos, George; Mentis, Andreas; Papaevangelou, Vasiliki; Gaitana, Katerina; Daponte, Alexandros; Hadjichristodoulou, Christos (BMC Public Health, 2012)
BACKGROUND: Toxoplasmosis is caused by infection with the protozoan parasite Toxoplasma gondii. Acute infections in pregnant women may be transmitted to the fetus and cause severe illness. The purpose of this study was to establish a dedicated surveillance network (DSN) for congenital toxoplasmosis (CT) in Greece, in order to assess the birth prevalence of CT. METHODS: A DSN of thirty clinicians was established for reporting CT cases from hospitals throughout Greece. The clinicians were selected on the basis that there was a high possibility the suspected cases would be referred to them from district hospitals or private clinics. Suspected cases of CT were reported on a monthly basis with a zero reporting card during a surveillance period from April 2006 to December 2009. A questionnaire was sent for any suspected case to record information including demographic parameters, clinical signs and symptoms and laboratory results. Serological and molecular confirmation of cases was performed by the Pasteur Hellenic Institute. All newborns suspected of CT received treatment and were serologically and clinically followed up for one year. RESULTS: The monthly response rate reached 100%, although only after reminders sent to 65% of the participant physicians. Sixty-three suspected CT cases were recorded by the DSN during the study period including fourteen confirmed and seven probable cases. Ten cases (47.6%) presented with symptoms at birth. Chorioretinitis was the most prominent manifestation, occurring in five symptomatic CT cases (50%). No other symptoms appeared by the end of the one year clinical follow up. No case was recorded by the existing surveillance system of the Hellenic Center of Disease Control and Prevention (HCDCP) during the same time period. Birth prevalence was estimated at 0.45, 0.51 and 0.51 per 10,000 births for 2007, 2008 and 2009 respectively. The incidence rate of symptomatic CT at birth was estimated at 0.10 cases per 10,000 births per year in Greece (for the period 2007-2009). CONCLUSION: The DSN for CT proved to be more sensitive than the classical notification system, easy in application and very efficient in reporting rare diseases such as CT. Similar DSNs could be used to provide useful information on other rare diseases.
Keywords: Congenital; Female; Fetal Death; Greece; Humans; Infant; Infectious Disease Transmission; Male; Newborn; Parasitic; Population Surveillance; Pregnancy; Pregnancy Complications; Toxoplasmosis; Vertical